Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/atmos12121707
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Associated with Total Suspended Particulate and Particulate Matter in Cement Grinding Plant in Vietnam

Abstract: Air pollution associated with suspended particles has become a significant concern in Vietnam recently. The study aimed to (1) investigate dust sources; (2) measure concentration levels of Total Suspended Particulate (TSP), Particulate Matter (PM) fractions; (3) identify silica levels and the correlation with respirable particles at a cement grinding plant in Vietnam. A total of 312 samples (52 TSP, 160 PMs) at 13 processes were measured using the direct-reading dust meter. The silica composition was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Similar high exposure events were noted in a study by Mirzaee et al, 29 where cement dust concentration was 4.5 mg/m 3 near the packing machine, 4.2 mg/m 3 during loading, 23 mg/m 3 for crushing, and 43–47.6 mg/m 3 in a raw mill. Thai et al, 30 suggest that the concentration levels of respirable cement dust concentration fluctuate significantly in different sections of the cement manufacturing industries, and such is dependent on the availability and levels of control mechanisms. A study by Couture et al, 31 in construction industry, showed high exposure levels of silica dust among crusher operators (0.08 mg/m 3 ) and concrete truck operators (0.01 mg/m 3 ), exceeding occupational exposure limits by more than 30 threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Similar high exposure events were noted in a study by Mirzaee et al, 29 where cement dust concentration was 4.5 mg/m 3 near the packing machine, 4.2 mg/m 3 during loading, 23 mg/m 3 for crushing, and 43–47.6 mg/m 3 in a raw mill. Thai et al, 30 suggest that the concentration levels of respirable cement dust concentration fluctuate significantly in different sections of the cement manufacturing industries, and such is dependent on the availability and levels of control mechanisms. A study by Couture et al, 31 in construction industry, showed high exposure levels of silica dust among crusher operators (0.08 mg/m 3 ) and concrete truck operators (0.01 mg/m 3 ), exceeding occupational exposure limits by more than 30 threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution is classified as another important problem of Thailand and this problem is currently more serious increasingly (Junpen et al, 2018). There are 2 major causes of air pollution including: human actions, for example, demands on energy for consuming in households, industries, and agriculture as well as air pollution caused by cars, ships, and planes that causes CO2, NO2, and hydrocarbons giving bad effects to human's health directly (Canha et al, 2021;Thai et al, 2021). Combustion of these types of fuel also increase the problems on air pollution every year; natural actions, for example, volcanic eruption causing high amount of dust and ash blowing in the air (Perera, 2018;Mperejekumana et al, 2021), wildfire causing smoke that is dangerous for respiratory system, decomposition of humus and carcass that may cause CO2, CH4, and NH3 in case of chemical reaction (Ray et al, 2019;Junpen et al, 2020); and dust caused by broken objects that would be distributed in the air when they are blown by the wind.…”
Section: Introductionmentioning
confidence: 99%